Undeveloped Oil and Gas Fields in the Industrializing World : A Description of Potential International Investment Projects for the Petroleum Industry - World Bank (Washington, DC, 2014)
Intensive exploration for oil, and gas, led to considering many discovered fields as non-commercial, which have since, not been developed. Yet, if developed, these fields could have significant economic impacts on a number of the Bank's borrowing countries. The study examines the undeveloped fields, the commercial potential, and contractual conditions under which these fields were discovered, and, in partnership with PetroConsultants, and Robertson Research, evaluates the likelihood for commercial viability. The study provides country-specific proposed changes, that if implemented, would ensure the commercial development of these otherwise marginal fields. Obviously, the private sector-oil companies would undertake commercial development, thus the study aims to assure the economic, and technical feasibility of those fields, and allow reconsideration by the industry, for development investment. Comparative data was obtained from the Study of World Wide Petroleum Contract Terms, the Africa Gas Initiative, the Gas Flare Reduction Project, and the International Finance Corporation's Potential African Carbon Trading projects. It is suggested that extraction of country-specific conclusions, be done by listing countries per type of Bank intervention, i.e., economic sector work; developed as part of a larger energy project; exploration promotion programs; gas market development; or technical assistance projects.